Einer hölzerner „Streitkolben” vom frühmittelalterlichen Gräberfeld von Bodzia bei Włocławek. Waffe oder Herrschaftssymbol? - Kara, Michał (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2016)
The article presents the results of an analysis of a grave from the late 10th century or the early 11th century, discovered in an early medieval cemetery in Bodzia in the eastern Kujawy region. The grave: unique not only by the cemetery’s standards, included, among other things, an oak club fitted in two bronze sheets. Comparative materials allow for interpreting it as the so-called insignia club (a kind of mace). It was an attribute of power used in medieval Europe at least since the 11th century by members of the highest secular and clerical elites, e.g. during armed expeditions. The preserved funeral inventory of the grave where the “club” was found indicates that a layman was buried there. Comparative materials used in the Bodzia find, also with respect to the function, is provided by the Bayeux Tapestry (northern France) woven in the 2nd half of the 11th century and presenting the battle of Hastings in 1066.